Murder, plain and simple - Alan, Isabella; Copyright Paperback Collection (Library of Congress) (New York, New York : Obsidian, 2013)
With her snazzy cowboy boots and her ornithophobic French bulldog, Angie doesn't exactly fit in with the predominantly Amish community in Rolling Brook, but her aunt's quilting circle tries to make her feel welcome as she prepares for the reopening of Running Stitch. On the big day, Angie gets a taste of success as the locals and Englisch tourists browse the store's wares while the quilters stitch away. But when Angie finds the body of ornery Amish woodworker Joseph in her storeroom the next morning, everything starts falling apart. With evidence mounting against her, Angie is determined to find the culprit before the local sheriff can arrest her. Rolling Brook always appeared to be a simple place, but the closer Angie gets to the killer, the more she realizes that nothing in the small Amish community is as plain as it seems.
Keywords: Amish -- Fiction; Murder -- Investigation -- Fiction; Quilting shops -- Fiction; Quilting -- Fiction; Ohio -- Fiction; Mystery fiction